IMPLEMENTASI MANAJEMEN KEARSIPAN DALAM MENINGKATKAN ADMINISTRASI SEKOLAH BIDANG TATA USAHA DI SMA NEGERI 1 CIBUNGBULANG BOGOR - Ima Rahmawati; Hana Lestari; Kikih Jakiah Darojah; Waslim Setiawan (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2023)
The purpose of this research is to find out the description of the application of filing management in the field of administration in an effort to improve school administration at SMA Negeri 1 Cibungbulang. This research is a field research using a qualitative descriptive approach. Data collection was carried out using the method of observation, interviews, and documentation. The data analysis technique in this study was carried out in two stages, namely first conducting analysis during the activity, namely by observing, interviewing and documenting, the second stage was analysis after the activity was completed which had three stages, namely data reduction, presentation, and drawing conclusions. The research results show; that with the implementation of good records management it can lighten the task or work of the administration section which will later have an impact on the realization of the goals of an agency, and have a major influence on administrative work such as making it easier to search and search for information or data needed so as to create a conducive work climate effective and efficient.